Impingement factors of rural library services on community lifestyle in Malaysia - Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Bolong, Jusang (Universiti Putra Malaysia Press, 2018)
This study attempts to provide a comprehensive overview of the impingement factors of rural library services on rural community lifestyle in Malaysia. The quantitative method is used in this study and a survey and distributing questionnaire are employed as the main instruments in collecting the data. A total of 400 rural communities that used 16 rural libraries are selected as the respondents using multi-stage cluster sampling. The results of the study show that all the factors studied, namely sources, services, access criteria and interaction have a positive and significant relationship with rural community lifestyle. Further analysis using multiple linear regression confirmed interaction as the factor that most contributed to developing the rural community lifestyle. A number of recommendations are highlighted that can assist the parties concerned in constructing the best strategies to further develop rural library services in Malaysia.